Penerapan Strategi Digital Bisnis pada UMKM di Desa Dilem Gondang Mojokerto - Apri Irianto; Onny, Widiar Onny Kurniawan; M. Nushron Ali Mukhtar; Aristha Purwanthari Sawitri (Universitas Muhammadiyah Malang, 2024)
Purpose – This service program aims to increase the application of digital technology in the Micro, Small and Medium Enterprises (MSME) sector which is increasingly important in the industrial era 4.0 to increase competitiveness and business sustainability. This research aims to analyze the implementation of digital business strategies in MSMEs in Dilem Gondang Village, Mojokerto. Design/methodology/approach – The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observation and literature study. Findings – The research results show that the majority of MSMEs in Dilem Gondang Village have started using digital technology, such as social media, marketplaces and digital financial applications, to support their marketing and business management. However, there are still challenges such as limited access to technology, low digital literacy, and a lack of competent human resources in managing digital-based businesses. Originality/value – This research recommends increasing digital training and education for MSME players, as well as support from local governments in providing adequate digital infrastructure. With the right digital strategy, MSMEs in Dilem Gondang Village are expected to be able to increase productivity, expand markets and contribute to regional economic growth.